Removal of reactive red 45 dye from aqueous solution using activated carbon developed from Catha edulis stem as a potential biosorbent - Tadele Mihret; Nigus Gabbiye; Bisratewongel Tegegne; Dessie Tibebe; Agegnehu Alemu (Scientific Reports)
Abstract Textile dyes pose considerable environmental problems, as they often contain harmful chemicals that contaminate the soil and water sources. This study investigated the use of activated carbon made from Catha edulis stems, a waste product from leaf consumption, for the biosorption of reactive red 45 dye. The khat stems underwent a carbonization process followed by chemical activation using phosphoric acid. Various analytical techniques were used to examine the material’s physical and chemical characteristics. Results showed that the activated carbon possessed diverse functional groups (FTIR), an amorphous internal structure with crystalline carbon regions (XRD), and a surface morphology featuring irregular shapes, pores, deep cavities, and holes (SEM). It also had a point of zero charge (pHpzc) of 4.82 and a high BET surface area of 496.316 m²/g. Batch adsorption experiments were conducted to assess dye removal efficiency and determine optimal removal conditions. The maximum removal efficiency of reactive red 45 dye was 94.5% under optimal conditions: pH 3.05, adsorbent dose 10.5 g/L, contact time 38.79 min, and an initial dye concentration of 50.4 mg/L. At these conditions, adsorption isotherm, kinetics, and thermodynamics were analyzed. The equilibrium data fit well with the Langmuir isotherm model and the pseudo-second-order kinetic model. These findings indicate that activated carbon developed from Catha edulis stem is a promising biosorbent for removing reactive red 45 dye from textile wastewater.